2017
DOI: 10.1111/jonm.12522
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to teamwork performance and stress of operating room nurses

Abstract: Aim: To evaluate operating room nurses' perception of teamwork performance and their level of mental stress and to identify related factors. Background:Little is known about the factors affecting teamwork and the mental stress of surgical nurses, although the performance of the surgical team is essential for patient safety. Methods:The questionnaire survey for operation room nurses consisted of simple questions about teamwork performance and mental stress. Multivariate analyses were used to identify factors ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 29 publications
4
64
0
9
Order By: Relevance
“…Performing safe surgery for patients is based on teamwork between members of the surgical team (34). Thus, for providing the best surgical care for the patient, team members must work together, communicate well, and coordinate (35). The results of the mentioned studies were in line with the third theme of this study, which stated that respecting colleagues and having a team spirit in the operating room are ethical skills.…”
Section: Discussionsupporting
confidence: 71%
“…Performing safe surgery for patients is based on teamwork between members of the surgical team (34). Thus, for providing the best surgical care for the patient, team members must work together, communicate well, and coordinate (35). The results of the mentioned studies were in line with the third theme of this study, which stated that respecting colleagues and having a team spirit in the operating room are ethical skills.…”
Section: Discussionsupporting
confidence: 71%
“…Due to DB, participants did not consider interactions between themselves and physicians as desirable, which was consistent with the study by Prati and Pietrantoni 2014 [35]. In his study, Sonada 2018 [25] had found working with a key person such as a surgeon and close relationship with him as one of the stressful team factors for a scrub nurse, in a way that DBs could redouble this stress.…”
Section: Discussionsupporting
confidence: 62%
“…How ORNs perceive and how they react to or deal with these behaviors? On the other hand scrub and circulating nurses are key members of ORs, they can play diverse, multifaceted, and specialized roles in these environments and work in direct relationships with surgeons, they can even have a significant impact on the overall team performance and surgical consequences [25,26].…”
Section: Operating Rooms Problem Behavior Operating Room Nursing Cmentioning
confidence: 99%
“…Psychological distress was reported to occur in nurses during the similar crisis, and it exacerbated the shortage of nurses due to mental illness, sick leave or resignation (Li et al., 2015). More importantly, poor psychological health among nurses might not only be detrimental to individual but also hinder professional performance and, in turn, the quality of nursing patients (Li et al., 2017; Sonoda, Onozuka, & Hagihara, 2018). Nursing for COVID‐19 patients was a high‐risk work, and any mistake in the process might lead to serious consequences, such as transmission of the novel coronavirus from patients to others in the hospital or disease condition deterioration of the COVID‐19 patients.…”
Section: Introductionmentioning
confidence: 99%